2010
DOI: 10.1002/jccs.201000190
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Prazosin, Atorvastatin, Rosuvastatin and Simvastatin in API, Dosage Formulations and Human Serum by RP‐HPLC

Abstract: Prazosin hydrochloride is the first developed selective antagonist for α1 — adrenoceptors, which is used as antihypertensive agent. Statins are used in the treatment of various types of hypercholesterolemia. In the present paper a simple, specific an accurate RP‐HPLC method was developed and validated for the simultaneous determination of prazosin, atorvastatin, rosuvastatin and simvastatin in active and in dosage formulations. A nucleosil 100‐10, C‐18, 10μ column having 250 × 4.6 mm i.d. in isocratic mode, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…After 24 hr, the remaining solution was employed to quantify simvastatin by an HPLC method using a 5 μm C8 column of 150 × 4.6 mm and with an UV‐detector working at a wavelength of 238 nm. The mobile phase was a methanol/acetonitrile/water mixture (70:10:30) adjusted to pH 2.5 with phosphoric acid and the flow rate was 1.0 mL/min (Sultana, Arayne, Shah, Shafi, & Naveed, ).…”
Section: Methodsmentioning
confidence: 99%
“…After 24 hr, the remaining solution was employed to quantify simvastatin by an HPLC method using a 5 μm C8 column of 150 × 4.6 mm and with an UV‐detector working at a wavelength of 238 nm. The mobile phase was a methanol/acetonitrile/water mixture (70:10:30) adjusted to pH 2.5 with phosphoric acid and the flow rate was 1.0 mL/min (Sultana, Arayne, Shah, Shafi, & Naveed, ).…”
Section: Methodsmentioning
confidence: 99%
“…In the light of the above results, ACE inhibitors may interact and effect a change in each other's availabilities. Methods were developed by HPLC for both ACE inhibitors and statins before starting interaction studies [85][86][87][88]. In vitro" interactions of ACE inhibitors with statins (atorvastatin, rosuvastatin, pravastatin and simvastatin) were studied in stimulated body environments utilizing the HPLC technique.…”
Section: Interaction Of Ace Inhibitors With Statinsmentioning
confidence: 99%
“…PRZ and CCBs are given in combination in the treatment of essential hypertension [10]. Boman et al [11] have suggested that addition of PRZ may be of value in patients with severe heart failure simultaneous determination of diltiazem and quinolones [28] and diltiazem with antidiabetic drugs [29] by HPLC.…”
Section: Introductionmentioning
confidence: 99%